Implementation of Social Assistance In Communities Affected by The Covid-19 Pandemic In Penawangan District Grobogan Regency Maqasid Al-Syariah Perspective - Luqman Nurhisam; Jaenal Arifin (Program Studi Hukum Keluarga Islam, 2022)
One form of government attention to the people affected by the Covid-19 Pandemic is by providing social assistance. The provision of social assistance is intended as an effort by the government to support community needs and restore health and nutrition. This study aims to examine and analyze the effectiveness of the distribution of social assistance to the community in Penawangan District, Grobogan Regency and examine it from the perspective of maqasid al-syariah. The type of method used in this study is sociological juridical with a qualitative approach. The main data sources were obtained through observation and interviews with informants, while the secondary data sources used books and articles. The data and information obtained were then processed using data analysis techniques in the form of descriptive qualitative. The conclusions of this study indicate that the distribution of social assistance has not been fully effective and fair because some of the assistance provided is not on target. Furthermore, when viewed from the maqasid al-syariah provision of social assistance by the government to the community can be said to be of benefit because it can preserve the soul (hifdz an-nafs) and restore the economy of the people affected by the Covid-19 pandemic in Penawangan District Grobogan Regency.Salah satu bentuk perhatian pemerintah terhadap masyarakat terdampak Pandemi Covid-19 yaitu dengan memberikan bantuan sosial. Pemberian bantuan sosial ini dimaksudkan sebagai upaya pemerintah guna menopang kebutuhan masyarakat serta pemulihan kesehatan dan gizi. Penelitian ini bertujuan untuk menelaah dan menganalisis efektivitas pendistribusian bantuan sosial pada masyarakat di Kecamatan Penawangan Kabupaten Grobogan serta mengkajinya dalam perspektif maqasid al-syariah. Jenis metode yang digunakan dalam penelitian ini adalah yuridis sosiologis dengan pendekatan kualitatif. Sumber data utama diperoleh melalui observasi dan wawancara dengan para informan, sedangkan sumber data sekunder menggunakan buku dan artikel. Data dan informasi yang diperoleh selanjutnya diolah dengan teknik analisis data berupa deskriptif kualitatif. Hasil kesimpulan penelitian ini menunjukkan bahwa pendistribusian bantuan sosial belum sepenuhnya berjalan efektif dan adil sebab beberapa bantuan yang diberikan tidak tepat sasaran. Selanjutnya apabila ditinjau dari perspektif maqasid al-syariah terhadap pemberian bantuan sosial oleh pemerintah kepada masyarakat dapat dikatakan bernilai kemaslahatan sebab dapat memelihara jiwa (hifdz an-nafs) dan pemulihan ekonomi masyarakat terdampak pandemi Covid-19 di Kecamatan Penawangan Kabupaten Grobogan.